Effectiveness of exergaming in improving functional balance, fatigue and quality of life in Parkinson's disease: A pilot randomized controlled trial. (May 2017) - Ribas, Camila Gemin; Alves da Silva, Letícia; Corrêa, Marina Ribas; Teive, Hélio Ghizone; Valderramas, Silvia
Abstract: Although motor symptoms in Parkinson's disease (PD) are well established, few studies have described the effects of exergaming on the clinical and functional outcomes of PD. Objectives: To analyze the effectiveness of exergaming in improving functional balance, fatigue, functional exercise capacity and quality of life in PD. Methods: The study population consisted of 20 patients (12 males and 8 females) aged 61 ± 9.11 years allocated into two groups: an exergaming group (EGG) (n = 10) and a conventional exercise, or control, group (CG) (n = 10). The following variables were evaluated: functional balance (Berg Scale), fatigue (Fatigue Severity Scale), functional exercise capacity (Six-Minute Walk Test) and quality of life (PDQ-39 Quality of Life Questionnaire). Results: RM-ANOVA showed that balance and fatigue differed significantly between time points: balance [F(1.29, 23.33) = 4.16, p = 0.043] and fatigue [F(2, 36) = 5.96, p = 0.006]. In both cases post hoc Bonferroni testing revealed an improvement after 12 weeks of exergaming (p = 0.033 and p = 0.000, respectively). However, this benefit was not sustained after 60 days of follow-up for either outcome. There were no differences in functional exercise capacity or quality of life between the two groups after 12 weeks of treatment. Conclusion: Exergaming was effective in enhancing balance and reducing fatigue in PD patients after 12 weeks of treatment, but this benefit was not sustained in the long-term. Highlights: A randomized pilot control trial on exergaming and conventional exercises. The balance, fatigue, exercise capacity and quality of life were evaluated. Improvement in balance and fatigue in exergaming group. However, those benefits were not sustained 60 days after treatment completion.